Strategic Human Resource Management: Linking Human Resource Management Strategy to Support Performance - Adelia Wahyu Tri Utami; Adelia Febrianti; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
Human resource management is crucial for establishing competitive advantage, recruiting, developing, and retaining top talent. Human resource strategy and organizational strategy are key determinants in facing increasingly complex global market challenges. Companies that can adapt and adopt innovative technologies in human resource management can improve operational efficiency, optimize recruitment processes, and provide a positive work experience for employees. Strategic human resource management is not solely the responsibility of the human resources department, but also of organizational leaders. Strong and committed leadership can develop human resources and create a solid foundation for long-term success. This study aims to examine the relationship between human resources and organizational strategy, as well as the inhibiting and supporting factors, and to determine the role of leadership in human resource management practices in improving organizational performance. The research employed a qualitative method, based on relevant previous research findings from the past five years and literature. The analysis revealed a relationship between human resource management practices, namely as a strategic and integrated framework that can enhance the achievement of organizational goals. Supporting and inhibiting factors in HRM practices lie in organizational management and human resource development. Furthermore, the role of leadership is crucial in managing human resources within an organization, as it can determine the direction and shared goals and achieve improved company performance.